‘Vaccine hesitancy’ among university students in Italy during the COVID-19 pandemic - Barello, Serena; Nania, Tiziana; Dellafiore, Federica; Graffigna, Guendalina; Caruso, Rosario (European journal of epidemiology, 2020)
The debate around vaccines has been in the spotlight over the last few years in Europe, both within the scientific community and the general public debate. In this regard, the case of the Italian vaccination debate is particularly worrying given that Italy has been one of the European countries with the highest number of measles cases in the recent past. According to this scenario, we conducted a cross-sectional study on a convenience sample of Italian university students aimed at: (1) exploring their attitudes towards a future vaccine to prevent COVID-19 and; (2) evaluating the impact of the university curricula (healthcare vs. non-healthcare curricula) on the intention to vaccinate. Descriptive analysis on the 735 students that answered to the question on the intention to vaccinate showed that 633 (86.1%) students reported that they would choose to have a vaccination for the COVID-19 coronavirus; on the other side, 102 (13.9%) students reported that they would not or be not sure to vaccine (low intention to vaccinate). This means that in our sample more than one student out of 10 shows low intention to vaccinate (vaccine hesitancy). Furthermore, when running analysis comparing healthcare students versus non-healthcare students we found no significant differences in responses’ percentage distribution ( p = .097). Understanding the student’s perspective about the future COVID-19 vaccine and supporting their health engagement and consciousness may be useful in planning adequate response and multidisciplinary educational strategies—including the psychological perspective on vaccine hesitancy underlying factors - in the post-pandemic period.